IOT Application in High Frequency Measurement - Ganesan, Vinondiran (2018)
In the light of impending Industry 4.0, there arises an urgency for the industry to embrace and take this head-on global change. Industry 4.0, which mainly underscores Internet of Things (IOT), Cyber-Physical System, and Smart Factory, allows the industry to leap forward in term of productivity by implementing automation in daily operation. In this study, the focus is shed on Internet of Things for the measuring field. The high frequency measuring instruments are important to fit the realization of Industry 4.0 since they could not be manipulated remotely and there is no exchange of data through cloud server. The function of semi-auto handler for high frequency measurement and characterization devices is much needed to provide a platform for Industry 4.0. Due to the absence of post processing tools, they are not capable to fully model device under test (DUT)’s behaviour in the term of data analysis. Thus, this issue can be solved using a wireless remote control of instruments where it uses a general platform. Besides that, a sensor will be integrated to this system to detect any error which can automatically trigger certain actions when the user is not around the area where the device under test is being analysed. The project also must be able to create notification to the user if there are any actions need to be done or if any automatic actions takes place so that user is aware of what is happening and to make sure correct data analysis is done.